2014
DOI: 10.1007/978-981-287-281-4_8
|View full text |Cite
|
Sign up to set email alerts
|

Control of Multilevel STATCOMs

Abstract: Control strategies suitable for multilevel STATCOMs are reviewed in this chapter. First of all, the models are systematically deducted and especial emphasis is given to the dynamic and steady state analysis in order to facilitate the study of the control techniques. Then, these control schemes aimed to achieve the overall compensation objectives are classified in linear and nonlinear approaches. In fact, among the linear alternatives, the Proportional-Resonant (PR) and the Proportional-Integral (PI) controller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Several authors have reported the use of STATCOM for the voltage and reactive power regulation with different configurations. For example, in larger power systems involving hundreds of buses, multipulse inverters based controllers are used because they provide lower harmonic distortion [ 5 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have reported the use of STATCOM for the voltage and reactive power regulation with different configurations. For example, in larger power systems involving hundreds of buses, multipulse inverters based controllers are used because they provide lower harmonic distortion [ 5 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%